Abuse of medicines for performance enhancement in sport: why is this a problem for the pharmaceutical industry?. (July 2012) - Elliott, Steve; Leishman, Barbara
The misuse of medicines for performance enhancement in sport (doping) is not approved by regulatory agencies, and is illegal in many countries. In addition to the 'traditional' doping agents such as steroids, β-blockers and blood transfusions, the list of agents and techniques used in doping is increasing and now includes newer medicines such as erythropoiesis-stimulating agents and growth hormones. Innovative new medicines are of particular interest as would-be dopers may believe them to be undetectable by current methods. Close collaboration between the biopharmaceutical industry and anti-doping agencies such as the World Anti-Doping Agency is critical to a successful anti-doping strategy. Industry is ideally placed to identify the doping potential of new medicines at early stages and to support early development of detection assays. A strong, united front between the biopharmaceutical industry and anti-doping agencies is essential to counter the misuse of medicines for performance enhancement, as well as to promote fair play and clean sport.